Proposed new interior design scheme of Spa Hydrotherapy for Grand Spa Hydrotherapy Sdn.Bhd. at NO.23, Jalan Mayang, Ampang, 50450 Kuala Lumpur / Nor Hidayah Salim - Salim, Nor Hidayah (Faculty of Architecture, Planning and Surveying, 2011)
The final project for the student of Diploma in Interior Design (INA 316) is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learnt from the basic to the final presentation on the proposed design. The project that had been chosen for the final project is to proposed a new interior design for the interior of Grand Spa Hydrotherapy, that is situated at No.23, Jalan Mayang, Ampang, 50450 Kuala Lumpur. This proposed spa is to attract more users to try for themselves the treatment that Grand Spa Hydrotherapy offered. At the same time to promote their product successfully as they offered a new technology treatment and interior, that is truly different from the other spa range, that mostly from Malaysia. The target market for the users of this spa is for everyone that are concern about their look, health and appearance. Furthermore, there is only one spa hydrotherapy in Malaysia which is located at G24A/B/C, Ground Floor, U-Mall, Jalan Pulai 20, Taman Pulai Utama, 81300 Skudai, Johor Bahru. So with this project it will introduce a spa hydrotherapy in Malaysia. The concept and image that had been chosen not only must be suitable with the clients as both of it would reflect the client and it products, but at the same time it would give a positive impact and increase the faith in the customers and the workers in Grand Spa Hydrotherapy. Before getting a desired design which is suitable with the client’s needs, some data analysis should be done where these analysis is on types of customers to attend the session, types of services offered, spaces to be conclude in the proposed area, operation time and information about other spa that use the same system in management, as the proposed spa. Some of the gained information of the study is through interviews, printed media, internet, observation and through the result from the case study either locally or internationally.